Postmodern Revivalism in US Entertainment Architecture. The Historical and Contemporary Context of Medievalism - Moeller, Nina (2023)
This thesis provides a historical and contextual analysis of themed architecture in postmodernity. I undertake a detailed architectural examination of the Excalibur Resort and Casino in Las Vegas, which opened in June 1990. By studying the building itself, archive material relating to its opening and relevant academic literature, I challenge the prevailing narrative that criticises the supposed absence of historical and geographical specificity in the themed architecture of the Las Vegas Strip. Scholars writing in the early 2000s, such as Bruce Bégout and Hal Rothman, regard the casino architecture of Las Vegas as superficial, artificial and detached from history and place; a narrative which continues into the literature of the 2020s as the position of, for example, Arthur Asa Berger demonstrates. This narrative is derived from the notion of pastiche that is dominant in scholarship on Postmodernism, such as in the work of Fredric Jameson, Umberto Eco, and Charles Jencks. It is further influenced by reductive readings of Robert Venturi, Denise Scott Brown and Steven Izenour’s discussion of Las Vegas in the now canonical Learning from Las Vegas (1972). By instead historicising the Excalibur’s materiality and ornamentation, its place, and its past and present cultural and political context, I demonstrate that the weight of detail pushes against the history-less view of architecture like the Excalibur. Deploying the theories of myth by Roland Barthes and Richard Howells I analyse the layered meaning of the medieval and the complex figure of King Arthur, their mythologising and their deployment in post-medieval times. I establish the casino in a long succession of buildings which combine Medieval Revival with contemporary architectural details to create engaging spaces reflective of their time. These spaces do not intend to produce copies, and indeed without a single ‘true’ source evaluating such architecture based on the criterion of authenticity is futile. Further, I argue by examining the casino’s interior that it demonstrates a strong connection to the art and heritage of the American Southwest, contrary to Marc Augé’s conception of such spaces as ‘non-places’. By considering the Excalibur’s performative elements like the tournament show, I conclude that it represents the wider socio-political background of late 1980s America. Popular and counterculture, political rhetoric, and anxieties, traditions and gender roles, as well as negotiations of history and place, are all legible in the architecture and décor of the Excalibur. Thus I argue that postmodern entertainment architecture can be understood as timely and politically reflective manifestations of myth rather than ahistorical pastiches, and that the Excalibur in particular presents a fascinating glimpse into the cultural politics of the time in which it was planned and built.